2015
DOI: 10.1371/journal.pone.0143216
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Expression of E2A-HLF Induces B-Cell Precursor Death and Myeloproliferative-Like Disease in Knock-In Mice

Abstract: Chromosomal translocations are driver mutations of human cancers, particularly leukemias. They define disease subtypes and are used as prognostic markers, for minimal residual disease monitoring and therapeutic targets. Due to their low incidence, several translocations and their biological consequences remain poorly characterized. To address this, we engineered mouse strains that conditionally express E2A-HLF, a fusion oncogene from the translocation t(17;19) associated with 1% of pediatric B-cell precursor A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
(54 reference statements)
2
3
0
2
Order By: Relevance
“…However, as we have failed to observe leukemia upon Hlf induction, even following extensive time periods, additional mechanisms other than aberrant activation of Hlf target genes seem crucial for E2A-HLF-mediated transformation. At the same time, our studies appear in line with the observed phenotypes of murine transgenic models of the E2A-HLF fusion that manifest with myelo- rather than lymphoproliferation ( Duque-Afonso et al., 2015 ).…”
Section: Discussionsupporting
confidence: 87%
“…However, as we have failed to observe leukemia upon Hlf induction, even following extensive time periods, additional mechanisms other than aberrant activation of Hlf target genes seem crucial for E2A-HLF-mediated transformation. At the same time, our studies appear in line with the observed phenotypes of murine transgenic models of the E2A-HLF fusion that manifest with myelo- rather than lymphoproliferation ( Duque-Afonso et al., 2015 ).…”
Section: Discussionsupporting
confidence: 87%
“…The t (17;19) Ранее на различных животных моделях было показано, что транслокации t(17;19) как единственного генетического события недостаточно для развития ОЛЛ [18,19]. В одном из исследований было показано, что экспрессия TCF3-HLF в гемопоэтических стволовых клетках приводит к летальному исходу на уровне эмбриона, в то время как экспрессия на уровне предшественников В-лим-…”
Section: рисунокunclassified
“…In addition, the conditional expression of E2A-HLF prevents apoptosis induced by cytokine withdrawal in interleukin (IL)-3-dependent mouse Ba/F3 cells (13). However, B-cell progenitor-specific conditional E2A-HLF knock-in mice exhibit hyposplenia and lymphopenia, whereas hematopoietic stem/progenitor cell (HSPC)-specific ones are embryonically lethal (14). The E2A-HLF fusion likely requires additional events to cause leukemia, since immunoglobulin enhancer and promoter-driven E2A-HLF transgenic and knock-in mice exhibit maturation arrest and apoptosis in cells expressing E2A-HLF (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…However, B-cell progenitor-specific conditional E2A-HLF knock-in mice exhibit hyposplenia and lymphopenia, whereas hematopoietic stem/progenitor cell (HSPC)-specific ones are embryonically lethal (14). The E2A-HLF fusion likely requires additional events to cause leukemia, since immunoglobulin enhancer and promoter-driven E2A-HLF transgenic and knock-in mice exhibit maturation arrest and apoptosis in cells expressing E2A-HLF (14)(15)(16). Numerous molecules downstream of E2A-HLF or cooperative with E2A-HLF have since been identified, including transcription factor Lim domain only 2 (LMO2), which is involved in T-cell ALL (17,18); snail family transcriptional repressor 2 (19); nuclear factor, interleukin 3 regulated (20); Groucho-related genes (21); Annexin VIII and sushi-repeat protein upregulated in leukemia, which have paraneoplastic roles in E2A-HLF-expressing leukemia (22); Zfp521 (23); survivin (24); and death receptors DR4/DR5 (25).…”
Section: Introductionmentioning
confidence: 99%